Coexisting severe frailty and malnutrition predict mortality among the oldest old in nursing homes: A 1-year prospective study. (May 2017) - Kamo, Tomohiko; Takayama, Keita; Ishii, Hideaki; Suzuki, Keisuke; Eguchi, Katsuhiko; Nishida, Yuusuke
Highlights: Coexisting severe frailty and malnutrition in nursing home are very frequent. Coexisting severe frailty and malnutrition are associated with mortality. It is necessary to pay attention to both functional and the nutritional status. Abstract: The aim of this study was to explore the relationship of coexisting severe frailty and malnutrition with all-cause mortality among the oldest old in nursing homes. This study was conducted among all subjects (n = 160) aged 85 years and older who lived in two nursing homes of Japan. Information about the health status of participants was gathered from history, medical documentation, test assessing frailty, according to the Canadian Study of Health and Aging-Clinical Frailty Scale (CSHA-CFS) and the Mini Nutritional Assessment Short Form (MNA-SF). Seventy five residents (46.9%) were identified as affected by coexisting severe frailty and malnutrition. After a 12-month follow-up period, 42 (26.3%) residents died. In the Cox regression analysis, coexisting severe frailty and malnutrition, and heart failure were associated with mortality during the 12-month follow-up period among the oldest old nursing home residents (adjusted HR 10.89, 95% CI 4.04–29.33, p < 0.0001; and adjusted HR 7.83, 95% CI 3.25–18.88, p < 0.0001, respectively). The present study suggests that coexisting severe frailty and malnutrition are very frequent, and coexisting severe frailty and malnutrition are associated with all-cause mortality among the oldest old in nursing homes.